Badania Instytutu Prahistorii UAM w Poznaniu na Tell Arbid (północno-wschodnia Syria) w latach 2008-2009 - Koliński, Rafał (Folia Praehistorica Posnaniensia, 2018)
In 2008 a new research project has been launched by the Institute of Prehistory, Adam Mickiewicz University of Poznań in the framework of Polish-Syrian Archaeological Mission to Tell Arbid. The objective of the project is to make extensive clearance of the remains identified previously in Sector SR at Tell Arbid as belonging to the post-Akkadian period (ca. 2150-2000 BC), a period of alleged abandonment and cultural collapse in the north-eastern part of Syria. Two seasons of fieldwork resulted in extensive exposure of the post-Akkadian structures, including several buildings, household and industrial installations (pottery kiln) as well as some graves. Among the findings, a considerable number of copper/bronze tools, implements and jewelry pieces are worth mentioning; the presence of numerous artifacts of copper/bronze and of a sandstone casting mould is suggestive of presence of a foundry at the site. Beside the post-Akkadian remains, an overlying level belonging to Habur Ware period (ca 1800-1700 BC) was explored. It featured mainly foundations of houses as well as a considerable number of graves dug into the surface of the tell. Among the graves, three family chamber graves stand out, because of their well-preserved construction, including a vaulted chamber, and an entrance shaft protected by a retention wall. One of these graves yielded a rich set of burial gifts, including weapons and other implements of copper/bronze, more than dozen pottery vessels and over 200 beads, as well as some semi-precious stones. Work at the site will be continued in 2010.